Pendampingan Kegiatan Pemasaran Produk Kemasan Berbahan Lele Segar dan Lele Asap - Indriati, Kumala; Mahyastuty, Veronica Windha; Mulyadi, Melisa; Silalahi, Agustinus (Jurnal Pengabdian Masyarakat Charitas, 2023)
In accordance with the theme of the 77th Independence Day of the Republic of Indonesia "Recover Faster and Rise More Strong", it is necessary to revive the community's economy. Organization KNPI (Indonesian National Youth Committee) with youth organizations others in the Cisauk sub-district are trying to encourage the revival of the economy society, especially MSMEs driven by organizations youth or by citizen units. The activity held is a bazaar which is entitled “Cisauk Youth Fest”. For the implementation of this activity the Faculty Atma Jaya Unika Engineering partners with BUMDES to provide assistance in preparation for BUMDES participation in the "Cisauk Youth Fest" bazaar, which was carried out at Gate 3 of the BSD Intermodal Modern Market. This activity is in collaboration with the the manager of the BSD Cisauk Intermodal Modern Market for the provision of a place.